STUDI KASUS PERILAKU KORUPTIF CALON PEGAWAI NEGERI SIPIL BIDANG KESEHATAN - Yulius Ramba (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2020)
Candidates for Civil Servants are employees who are declared to have passed the selection for admission of civil servants who need to be equipped with moral integrity, honesty, spirit and motivation of nationalism and nationality, superior and responsible personality traits, and strengthening professionalism and competence in the field, to realize services based on values. Accountability value, Nationalism, Public Ethics, Quality Commitment, and Anti Corruption. The problem in this research is whether the participants in the basic training of the Candidate for Civil Servants have / have been involved in corrupt behavior in their respective workplaces and whether there are factors in the work environment that support the opportunity for corrupt behavior to occur. The purpose of this research is to find out whether candidates’ civil servants from health workers are involved or not involved in corrupt behavior in their workplace before participating in training, to be used as a basis for taking adjustments to learning anti-corruption material in order to close the gap for possible behavior corruptive. This research method uses a qualitative approach, which describes the characteristics of a particular group, using an ethnomethodology approach, namely how to study social behavior by describing it as it is, observing in detail about the practice of daily life. The results of the research obtained show that health workers with the status of prospective civil servants have been involved in acts of corruption, take inventory items, goods to support services, and receive gifts from the people served, even though they feel unaware that these actions are corrupt. Furthermore, it is necessary to develop and adjust anti-corruption material for the basic training participants for health personnel civil servant candidates.